Self-Esteem among Men Who Have Sex with Men Living with HIV: A Qualitative Study - Linlin Lindayani; Ridzki, Melinda Patricia; Purnama, Heni (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: HIV transmission in males, particularly in Indonesia, is increasing due to increased sexual activity among Men who have Sex with Men (MSM) groups. This is largely due to diminished self-esteem and reluctance to disclose their status, influenced by factors like power, virtue, relevance, and competence. Aims: The study investigates the self-esteem of MSM living with HIV and explores the factors that may influence their self-esteem. Methods: This study employs a descriptive qualitative study. The study used interviews and content analysis techniques to gather data on HIV individuals at the Public Health Center, specifically focusing on MSM. Results: The interview data revealed six themes: individualism, body image dissatisfaction, lack of motivation, lack of peer support, aspiration to be useful, and self-esteem needs. Conclusion: The study reveals that self-esteem in HIV-positive men is influenced by coping strategies, body image dissatisfaction, motivation, and peer support. It suggests helping others and enhancing library resources, regular investigations, and a specialized counseling program to improve self-esteem.